Analysis of Body Work Posture in Midwives During Placental Retention - Firdaus Ashari; Rohmat Subodro (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2023)
The midwife's working posture when taking the placenta attached to the uterus of the laboring mother manually shows the body's posture which can cause musculoskeletal disorders. This research aims to know and study the assessment of the REBA method for midwife workers' posture in the prevention of musculoskeletal disorders. This research method is a type of observational analytic study that uses descriptive qualitative in total sampling among midwife workers. Data was collected using a REBA sheet. The results showed the results of the assessment using REBA with a final score of 13 has a level of risk